Analysis of United States Propaganda Against North Korea Through The Film The Interview - Jessi Monika (International Journal on Social Science, Economics and Art, 2021)
This research tried to describe the propaganda made by United States against North Korea through a movie entitled The Interview. The movie Interview. The movue despict how the communist state of North Korea is very closed and anti to foreign countries eventually want to do an interview with the president of North Korea. In the film The Interview United States producing films on large-General for the state of North Korea, where the United States and North Korea opposites in many ways, both in terms of economics, ideology, and the perception of the public, even in the use of nuclear weapons. The theory used in this research is to analyze the theory of discourse analysis Norman Fairclough, to understand the views of experts on the analysis of discourse, the concept of propaganda techniques according to the experts to understand the propaganda. By using interviews with respondents drawn by profession, this study uses analysis of the interview, the general condition of the two countries, critical discourse analysis, and examined the scene and its relevance to theories and concepts used. The overall results were obtained that the film is a propaganda film The Interview United States against North Korea, one of the film's release purpose is to divert North Korea at the same time prevent North Korea did not attack the United States with nuclear weapons.